Uma proposta, duas experiências : a Fundação Rockefeller e a formação de enfermeiras no Brasil e na Argentina (primeira metade do século XX) - Korndörfer, Ana Paula (Descentrada. Revista interdisciplinaria de feminismos y género.)
This text aims to discuss the role of the International Health Division (IHD) of the Rockefeller Foundation (RF), a North American philanthropic institution, in the training of nurses in Brazil and Argentina in the first half of the 20th century. The article, which includes a historiographical discussion and analysis of sources produced, for example, by the Foundation itself, is divided into three parts. In the first section, some conceptions of the IHD around modern nursing are shown. In the last two, the training of nurses in the two countries in question is addressed, highlighting similarities and differences.